Lets say we have (-4)^3, does this mean (-4)*(-4)*(-4) or -(4*4*4) 

3 Answers

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

The value of (-4)^3 has to be determined. Use the order of operators specified by BODMAS. First, deal with the brackets and do whatever is specified in the brackets. Then raise it to the exponents.

If y = -4, (-4)^3 = y^3 = y*y*y = (-4)*(-4)*(-4) = - 64

In this case (-4)^3 = (-4)*(-4)*(-4) = -(4*4*4) though that may not always be true.

The value of (-4)^3 = -64.

User Comments